Treatment adherence and short-term outcomes of smoking cessation outpatient clinic patients - Dilek Karadoğan; Özgür Önal; Deniz Say Şahin; Yalçın Kanbay; Sebih Alp; Ünal Şahin (Tobacco Induced Diseases, 2018)
Introduction Previous studies have shown that adherence to treatment is fundamental to success in smoking cessation. However, smoking cessation medication regimens are limited significantly by the struggle to adhere to them. This study was conducted to evaluate the factors associated with treatment adherence and quitting success in a group of patients that applied to our smoking cessation outpatient clinic (SCC).